Extracellular vesicles in osteoarthritis synovial fluid contain both transmembrane and intravesical TNF-α - Xin Zhang; Virginia Byers Kraus (Osteoarthritis and Cartilage Open)
Objective: We previously identified extracellular vesicles (EVs) as a key source of TNF-α in the plasma of both knee osteoarthritis (OA) patients and healthy individuals. Building on these findings, this study aimed to evaluate the presence of surface-bound transmembrane TNF-α (TM-TNF-α) and intravesical TNF-α in EVs from OA synovial fluid (SF). Methods: Using high-resolution flow cytometry, we rigorously quantified the percentages and integrated mean fluorescence intensity (iMFI) of surface-bound, intravesical, and total TNF-α forms in EVs isolated from SF of 25 knee OA patients. CZ CELLxGENE and OA joint tissue-derived single-cell and single-nuclei RNA sequencing data were used to analyze TNF gene expression. Results: TNF is expressed across multiple cell types. In OA joints it is predominantly expressed by synoviocytes, with TNF-α present in the SF EV pool. TM-TNF-α was consistently detected on SF EVs using three distinct TNF-α antibodies, although its frequency and iMFI were significantly lower than the corresponding intravesical TNF-α (Friedman test with Benjamini-Hochberg correction, FDR <0.05). The average percentages (and range) of EVs expressing TNF-α, as detected by the three anti-TNF-α antibodies, were 2.57 ​% (0.09–37.08 ​%) for TM-TNF-α+, 8.62 ​% (0.38–43.64 ​%) for intravesical TNF-α+, and 14.42 ​% (0.71–44.32 ​%) for total EV TNF-α+. Interestingly, TM-TNF-α frequencies on SF EVs were similar to those observed on various immune cell subsets in peripheral blood. Conclusions: While intravesical TNF-α may evade TNF-α inhibitors, TNF-α carried by EVs retains pathogenic potential, either by activating pro-inflammatory pathways via TM-TNF-α receptor engagement on target cells, or through the transfer of TNF-α cargo to recipient cells.